Predicting Adverse Pregnancy Outcomes in First Time Mothers: The Role of Maternal Body Mass Index: First-Time Mothers: The Role of Maternal Body Mass Index - Aziz, Amna; Tabassum, Shagufta; Raza, Kanwal; Rana, Adeela Anwar; Shahbano, .; Karim, Sajilah (Pakistan Journal of Health Sciences, 2025)
Maternal underweight during pregnancy can profoundly "programme" the fetal physiology and metabolism, which may end up in chronic illnesses later in life. including diabetes mellitus, cerebrovascular disease and hypertension. Objective: To figure out the likelihood of untoward events among underweight nulliparous women. Methods: A descriptive cross-sectional study was performed in the Obstetrics and Gynaecology Department, Nishtar Hospital, Multan, for the period of four months from December 2024 to March 2025 using non-probability consecutive sampling. Around 401 women were included after fulfilling the selection criteria. Data were collected through a specialized form and reviewed using SPSS Version 20.0. Results: Mean age was 28.98 ± 4.21 years among the participants. Mean height was 165 ± 7.43 centimeter, and mean weight was 52.21 ± 3.25 kilograms. Mean body mass index (BMI) was 18.11 ± 0.23 kg/m2.Cesarean delivery was reported among 73 (18.2%), pre-eclampsia in 57 (14.2%), preterm delivery in 165 (41.1%) and low-birth-weight babies were 126 (31.5%). Conclusions: The results reported an upsurge in the incidence of undesirable pregnancy outcomes such as preterm births and low birth weight babies among underweight first-time mothers. Proper counselling of these cases regarding weight gain before conception can help to lessen these adverse events and can be helpful in subsequent pregnancies.